2010
DOI: 10.1111/j.1538-7836.2009.03498.x
|View full text |Cite
|
Sign up to set email alerts
|

Mean platelet volume is a risk factor for venous thromboembolism: the Tromsø study

Abstract: Summary. Background: Platelet size, measured as mean platelet volume (MPV), is associated with platelet reactivity. MPV is increased in acute myocardial infarction, and has been identified as an independent risk factor for future myocardial infarction and stroke. Objectives: The purpose of the study was to determine the impact of platelet count and MPV on the incidence of venous thromboembolism (VTE) in a prospective, population-based study. Methods: Platelet count, MPV and baseline characteristics were regist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
252
7
13

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(290 citation statements)
references
References 33 publications
8
252
7
13
Order By: Relevance
“…Incident VTE events among the study participants were recorded from the date of enrollment (1994‐95) until December 31, 2012. For each potential VTE case the medical records were reviewed by trained personnel, and VTE events were adjudicated and recorded when clinical signs and symptoms of DVT or PE were combined with objective confirmation by radiological procedures, and resulted in a VTE diagnosis requiring treatment, as described in detail previously 19. The University Hospital of North Norway is the only hospital serving the Tromsø region, and all relevant diagnostics and hospital care are provided by this hospital.…”
Section: Methodsmentioning
confidence: 99%
“…Incident VTE events among the study participants were recorded from the date of enrollment (1994‐95) until December 31, 2012. For each potential VTE case the medical records were reviewed by trained personnel, and VTE events were adjudicated and recorded when clinical signs and symptoms of DVT or PE were combined with objective confirmation by radiological procedures, and resulted in a VTE diagnosis requiring treatment, as described in detail previously 19. The University Hospital of North Norway is the only hospital serving the Tromsø region, and all relevant diagnostics and hospital care are provided by this hospital.…”
Section: Methodsmentioning
confidence: 99%
“…An increase in the mean platelet volume (MPV) is seen in vascular events such as atheroscherosis, acute syndromes, venous and arterial thrombosis, or thromboembolism [20][21][22] . Previous reports have investigated the relationship between MPV levels and ISSNHL.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with conditions that have been considered to influence platelet indices were excluded from the study. Exclusion criteria were: (1) previous thromboembolism, (2) known malignancy, (3) immobilization, (4) inability to attend follow-up visits, (5) pregnancy, (6) ventricular systolic dysfunction, (7) trauma, (8) a new previous surgical operation, (9) atrial fibrillation, (10) obesity, (11) arterial stroke, (12) peripheral vascular disease, (13) infection, (14) acute coronary syndromes, (15) chronic renal or hepatic diseases, (16) diabetes mellitus, (17) acute and chronic PE and (18) recurrent episode of DVT. Control group consisted of patients with uncomplicated primary varicose veins of the lower limbs.…”
Section: Study Populationmentioning
confidence: 99%
“…Previous studies have shown platelet reactivity in patients with PE and DVT [7][8][9][10][11][12]. Mean platelet volume (MPV) is a measure of average platelet size [13,14].…”
Section: Introductionmentioning
confidence: 99%